Gerenciamento de dados em agricultura de precisão - Alberton, William Luis (2019)
With the technological evolution, aware need to improve devices and tools to enable better management of activities and consequently maximize the results obtained. The use of technology in the agribusiness sector brings with it new concepts and different ways of managing the most diverse activities. Technologies such as GPS allow farmers to demarcate their properties, create maps of their crops and make comparisons before and after harvesting, and enable the practice of precision agriculture. Precision agriculture consists of field activity management practices aimed at optimizing the use of agricultural inputs, thereby increasing production capacity and reducing the impact on the environment. For this, it uses management systems, which are responsible for recording, measuring, managing and analyzing geographically referenced information or data. These systems are developed through the use of programming languages and tools for system development. Aiming to encourage the adoption of precision farming practice, this work aimed at creating a precision agriculture data management system in a Web environment, accessible through any computer or mobile device with Internet access. Using the latest technologies for WEB, such as the JavaScript language and the Angular Framework 7, it was possible to develop a fast and consistent system. Through this system, the user has the possibility to manage the most diverse aspects of rural property, having control over the activities carried out in the field, such as machine operations, seed operations, supplies, delivery, among others. From the management of these operations, the user has a base of historical information, available through the visualization of reports and graphs, allowing a more assertive analysis of the strategic decision making. This system integrates a larger project, called AgDataBox, which consists of independent modules that share an API and a common database. Thus, data collected directly from the field by sensors or mobile applications are sent to the shared API, making them available in real time, thus reducing the boundaries of knowledge from integrated management.